ALV-J-contaminated commercial live vaccines induced pathogenicity in Three-Yellow chickens: one of the transmission routes of ALV-J to commercial chickens - Wang, Peikun (Poult Sci, 2021)
One avian leukosis virus of subgroup J (ALV-J) strain GX14YYA1 was isolated from a commercial bivalent Newcastle disease (ND)–infectious bronchitis (IB) vaccine in our previous study. To evaluate the pathogenicity of the ALV-J-contaminated vaccine on commercial chickens, day-old Three-Yellow chicks in group I were vaccinated with ALV-J-contaminated bivalent ND-IB live vaccine by intranasal and eye drop at 1-day-old for the primary vaccination and at 7-day-old for the secondary vaccination. Groups II and III were kept as the normal vaccination group with the noncontaminated ND-IB vaccine and blank control groups, respectively. The birds of different groups were maintained separately in isolators for 175 d. The first viremia was detected at 4 wk of age and 20% (2/10) of the birds maintained viremia during 11 to 25 wk of age. At the same time, the birds in group I experienced a significant suppression of body weight gain when compared with those of groups II and III (P < 0.05). In addition, the birds in group I showed obvious ALV-J hemangioma-type anatomical lesions in the liver and tumors were observed in the abdominal cavity. The results demonstrated that the ALV-J contaminated commercial live vaccines can induce pathogenicity in commercial Three-Yellow chickens and indicate that ALV-J-contaminated commercial live vaccines could be one of the transmission routes of ALV-J to commercial chickens.